Local area variation in health visiting contacts across England for children under age 5: a cross-sectional analysis of administrative data in England 2018-2020 - Liu, Mengyun; Woodman, Jenny; Mc Grath-Lone, Louise; Clery, Amanda; Bunting, Catherine; Bennett, Samantha; Kendall, Sally; Kirman, Jennifer; Weatherly, Helen; Barlow, Jane; Bedford, Helen; Harron, Katie (International Journal of Population Data Science, 2024)
Background The health visiting service in England leads the government's Healthy Child Programme (HCP) for children under five years. Local authorities and their provider partners deliver this service differently across England. Objective To describe local authority variation in the delivery of health visiting to children under five years in England (2018-2020). Methods We used publicly available statistics on mandated health visiting contacts, and administrative data from the Community Services Dataset (CSDS) on duration, location, and medium of contacts. We mapped population coverage of mandated contacts (new birth visit, 6-8-week review, one-year review, and 2-2½ -year review) and described the frequency and characteristics of mandated and additional contacts across local authorities. Results Based on publicly available data, almost all eligible children received their new birth visit, 6-8-week review and one-year review (89%-99%), with substantial variation across local authorities in children receiving he 2-2½ -year review: median 81%, range 33%-98%. Based on CSDS, 80% of local authorities (n=46/57) delivered more additional than mandated contacts: a median of 1.6 additional contacts (range: 0.1-8.5) were delivered for each mandated contact. There was also significant variation in the duration of contacts and the percentage of contacts delivered face-to-face and at home. Conclusions Despite decreases in funding and workforce since 2015, in 2018–2020, health visiting teams reached nearly all babies and most children face-to-face via mandated contacts, and conducted over one and a half times the number of additional contacts relative to mandated contacts, with variation between local areas. This represents a significant public health infrastructure to support the health and development of babies and children and the wellbeing of their families in the critical period before school. Our study highlights the importance of taking into account additional contacts. Further work is needed to understand variation, including in the way additional contacts are used.